The Use of Corporate Financial Statements and Related Data by Organized Labor (Book). - Dubin, Robert (The Accounting Review, 1955)
Reviews the book "The Use of Corporate Financial Statements and Related Data by Organized Labor," by Wilbur F. Pillsbury.